Fast reconstruction of SMS bSSFP myocardial perfusion images using noise map estimation network (NoiseMapNet): a head-to-head comparison with parallel imaging and iterative reconstruction - Adam, Naledi Lenah; Kowalik, Grzegorz; Tyler, Andrew; Mooiweer, Ronald; Neofytou, Alexander Paul; McElroy, Sarah; Kunze, Karl; Speier, Peter; Stäb, Daniel; Neji, Radhouene; Nazir, Muhummad Sohaib; Razavi, Reza; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Simultaneous multi-slice (SMS) bSSFP imaging enables stress myocardial perfusion imaging with high spatial resolution and increased spatial coverage. Standard parallel imaging techniques (e.g. TGRAPPA) can be used for image reconstruction but result in high noise level. Alternatively, iterative reconstruction techniques based on temporal regularization (ITER) improve image quality but are associated with reduced temporal signal fidelity and long computation time limiting their online use. The aim is to develop an image reconstruction technique for SMS-bSSFP myocardial perfusion imaging combining parallel imaging and image-based denoising using a novel noise map estimation network (NoiseMapNet), which preserves both sharpness and temporal signal profiles and that has low computational cost.The proposed reconstruction of SMS images consists of a standard temporal parallel imaging reconstruction (TGRAPPA) with motion correction (MOCO) followed by image denoising using NoiseMapNet. NoiseMapNet is a deep learning network based on a 2D Unet architecture and aims to predict a noise map from an input noisy image, which is then subtracted from the noisy image to generate the denoised image. This approach was evaluated in 17 patients who underwent stress perfusion imaging using a SMS-bSSFP sequence. Images were reconstructed with (a) TGRAPPA with MOCO (thereafter referred to as TGRAPPA), (b) iterative reconstruction with integrated motion compensation (ITER), and (c) proposed NoiseMapNet-based reconstruction. Normalized mean squared error (NMSE) with respect to TGRAPPA, myocardial sharpness, image quality, perceived SNR (pSNR), and number of diagnostic segments were evaluated.Results: NMSE of NoiseMapNet was lower than using ITER for both myocardium (0.045±0.021 vs. 0.172±0.041, p<0.001) and left ventricular blood pool (0.025±0.014 vs. 0.069±0.020, p<0.001). There were no significant differences between all methods for myocardial sharpness (p=0.77) and number of diagnostic segments (p=0.36). ITER led to higher image quality than NoiseMapNet/TGRAPPA (2.7±0.4 vs. 1.8±0.4/1.3±0.6, p<0.001) and higher pSNR than NoiseMapNet/TGRAPPA (3.0±0.0 vs. 2.0±0.0/1.3±0.6, p<0.001). Importantly, NoiseMapNet yielded higher pSNR (p<0.001) and image quality (p<0.008) than TGRAPPA. Computation time of NoiseMapNet was only 20s for one entire dataset.NoiseMapNet-based reconstruction enables fast SMS image reconstruction for stress myocardial perfusion imaging while preserving sharpness and temporal signal profiles.